Pelatihan Pembuatan Stiker Kreatif sebagai Media Promosi untuk Meningkatkan Branding dan Penjualan UMKM di Kelurahan Pagesangan, Surabaya: Pengabdian - Eli Retnowati; Nur Aniqa Pernaningtik; Eliya Putri Aprilia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Creative sticker design training as a promotional medium is one of the empowerment strategies for Micro, Small, and Medium Enterprises (MSMEs) to enhance branding and sales. This activity was conducted in Pagesangan Subdistrict, Surabaya, aiming to raise MSME actors' awareness of the importance of packaging design and product branding through the use of graphic design technology such as Canva. The method employed was Participatory Action Research (PAR), involving active community participation in all stages, from problem identification to activity evaluation. The training was attended by approximately 30 participants over five days, consisting of material presentation, technical training, and evaluation. The results showed that participants gained understanding and skills in designing attractive stickers aligned with their product identity. This led to increased branding awareness, product appeal, and the potential for higher sales. Through this training, MSME actors became more independent in visual promotion efforts and better equipped to strengthen their brand presence in a competitive market.